Empowerment through ecoprint training on mugs for PKK women in Gampong Bayeun, East Aceh Regency - Ismanidar, Nur; Chandra, Riny; Salman, Salman (Community Empowerment, 2025)
The challenges faced by the PKK group include limited knowledge and skills in utilizing local natural resources for creative products, a lack of understanding regarding simple business management, and low utilization of digital marketing. To address these issues, the activity was conducted using an Asset-Based Community Development (ABCD) approach, which emphasizes leveraging local assets in the form of leaves and flowers, human resource capacity, and community social networks. The activity was carried out through several stages: coordination, socialization, technical ecoprint training on ceramic mug media using the steaming method, group practice, provision of business management knowledge, introduction to digital marketing, and evaluation. The results show that the participants successfully created natural-patterned ecoprint mug products, developed a better environmental awareness, and acquired basic entrepreneurial skills, including calculating the cost of goods sold and determining the selling price. The PKK women are now capable of producing approximately $±20$ ecoprint mugs per month with 3–5 variations of motifs. Thus, this activity not only enhances creative skills and entrepreneurial literacy but also opens up opportunities for women's economic empowerment based on local potential.